Penggunaan integer linier programming untuk meminimumkan ruang kuliah pada Mata Kuliah Dasar Umum (MKDU) Studi Kasus di Universitas Tribuana Kalabahi - Damaris Lalang; Dewi Rosalina Alohaja (Saintek Lahan Kering, 2021)
Scheduling courses is one of the problems that are often experienced by a university. The same is true for Tribuana Kalabahi University (UNTRIB). The scheduling of courses at UNTRIB consists of two scheduling schemes, namely scheduling of Study Program courses and scheduling of General Basic Courses. Scheduling of Study Program Courses is arranged by the Study Program while for MKDU it is arranged by a team in the MKDU unit at the beginning of each semester. The scheduling process is done manually, by taking the schedule of courses in each Study Program at UNTRIB, after that MKDU begins to arrange course scheduling by adjusting the scheduling of courses from existing study programs. Integer linear programming (ILP) is a method that can model scheduling problems with various constraints that can be adapted to the needs of the University, and ILP can be used to make MKDU scheduling using Lingo 11.0 software. The purpose of this study is to minimize the lecture hall so that there are no clashes during lectures. From the results of this study, it was stated that initially using 20 lecture rooms, it could be converted into 5 lecture rooms with adjusted time slots